2013
DOI: 10.3892/ijmm.2013.1377
|View full text |Cite
|
Sign up to set email alerts
|

Salt-inducible kinase 1 is involved in high glucose-induced mesangial cell proliferation mediated by the ALK5 signaling pathway

Abstract: Abstract. High glucose levels can induce mesangial cell proliferation and extracellular matrix (ECM) accumulation through the type I activin receptor-like kinase 5 (ALK5) signaling pathway. Salt-inducible kinase 1 (SIK1) prevents fibrosis by downregulating ALK5, while the expression level of the SIK1 protein itself is downregulated by glucose in neuronal cells following ischemia. In this study, we investigated the correlation between SIK1 and the ALK5 signaling pathway in a rat glomerular mesangial cell line (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 34 publications
7
21
0
Order By: Relevance
“…This is obviously the first report that suggests the potential of adenovirus-mediated SIK1 gene transfer in the management of hyperglycaemia in the HFD/STZ-induced T2DM rat model. More importantly, we for the first time demonstrated that SIK1 mRNA and protein expression were significantly reduced in the livers of HFD/STZ-induced diabetic rats, which was consistent with our previous in vitro studies [8, 18], suggesting that the expression of SIK1 is inhibited in diabetic states.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is obviously the first report that suggests the potential of adenovirus-mediated SIK1 gene transfer in the management of hyperglycaemia in the HFD/STZ-induced T2DM rat model. More importantly, we for the first time demonstrated that SIK1 mRNA and protein expression were significantly reduced in the livers of HFD/STZ-induced diabetic rats, which was consistent with our previous in vitro studies [8, 18], suggesting that the expression of SIK1 is inhibited in diabetic states.…”
Section: Discussionsupporting
confidence: 92%
“…The Thr182 of SIK1 is phosphorylated by LKB1, resulting in conversion from inactive SIK1 to the active form [6]. Consistent with previous in vitro observations [8, 18], this in vivo study indicated that the level of Thr-182 phosphorylation, as well as the expression of SIK1 mRNA and protein, was downregulated in the livers of HFD/STZ-induced diabetic rats, suggesting that the SIK1 kinase activity may be suppressed in diabetic states. As expected, Ad-SIK1 treatment significantly elevated the level of pT182 SIK1 compared to the DM group.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Then tumors were removed from mice and the tumor weight was recorded immediately. IHC was performed as previously described [54, 55]. …”
Section: Methodsmentioning
confidence: 99%